A ressocialização na perspectiva das egressas prisionais atendidas pelo patronato municipal de Foz do Iguaçu-PR - Sousa, Cyrce Adryadne (2016)
This work aims to analyze, from the perspective of ex-offenders, if the rehabilitation process carried out by the prison and later by the Municipal Patronage of Foz do Iguaçu/PR is in line with they expectations as well as what may be missing in this process, by analyzing the speeches of the ex-offenders and what is provided by law. Although it is undeniable the impact of education and work in the rehabilitation process, such factors should be considered together with others which need to be adjusted to prevent new criminal incidence such as: involvement and acceptance of the community and the family, combating drug use, meeting the basic demands of material assistance, among others. This study addresses the female prison situation in the city of Foz do Iguaçu in 2015, articulating the previous data of Paraná and Brazil in order to triangulate information and discuss the issue. The resocialization policies in Brazil, as well as those specific to the female audience, are adressed in order to analyze the fundamentals of the Penal Execution Law on the rehabilitation in individual form and also the factors that can lead to criminal incidence, through the study of theoretical concepts of academically recognized authors and in dissertations and theses. Finally, the data collected from the ex-offenders attended by the Municipal Patronage of Foz do Iguaçu/PR is analyzed, and it indicates that the poorest female population may be the most imprisoned in the city, as a result of the policy promoted by the state repression as apparatus of neoliberalism. The ex- offenders report little understanding of what rehabilitation process means, demonstrating that there is no clarity and correspondence between what the state seeks and what ex-offenders understand as necessary for the return to social life, demonstrating that the State’s speech about resocialization hides repressive practices and the post-prison care just becoming an assisted control mechanism.